Where the red fern grows - Rawls, Wilson (New York : Delacorte Press, 2016)
A young boy living in the Ozarks achieves his heart's desire when he becomes the owner of two redbone hounds and teaches them to be champion hunters.
Keywords: Hounds -- Fiction; Dogs -- Fiction; Hunting -- Fiction; Ozark Mountains -- Fiction